EVALUASI ATAS PERLAKUAN PERPAJAKAN TERHADAP TRANSAKSI TRANSFER PRICING PADA PERUSAHAAN MULTINASIONAL DI INDONESIA - NURHAYATI, INDAH DEWI (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract : Transfer pricing is a term for a pricing mechanism that is not fair on the transaction supply of goods or delivery of services by those who have a special relationship (related parties). Transfer pricing is usually done multinationals companies. With such unfairly practices, resulting in the potential loss of tax that should be accepted, that manipulative activity is often associated with loss of state. In fact, the case of transfer pricing is actually not the first time it happened. It has long been the haunt of cases, even in the realm of taxation is not only the country, but also other countries in the world. Based on data from Organization for Economic Cooperation and Development (OECD), 60% of total world trade in transfer pricing practice indicated. To manage this, the Directorate-General (DG) Tax Ministry of Finance is now updating the draft regulations focus on the Pricing. This draft as part of a strategic policy at 2013, that improved their capacity to cope with any issues abaout Transfer Pricing. Key words: transfer pricing, multinational companies, tax avoidance, tax rules